The Autobiography of Juozas Miltinis: Text and Context - Mikelinskaitė, Angelė (Bibliotheca Lituana, 2019)
The author of this article offers a discussion and comparison of Juozas Miltinis’s (1907–1994) view of his own personality and his attitude toward his identity and reveals the variation of his genesis, based on the Director’s three surviving autobiographical texts. The biographical facts are presented in the autobiography written during WWII and the Soviet period, revealing the relationship of the person with his era.
Keywords: Juozas Miltinis; autobiographies; comparative method